Cartoon Crazys - Spooky Toons - Sparber, Isidore; Kneitel, Seymour; Goldstone, Duke; Iwerks, Ub; Fleischer, Dave (Winstar, 2000)
"Spooky Toons" culls 13 vintage cartoons, each centering on some poor bug-eyed creature contracting a usually misguided case of the creeps. To say it's fraught with the sort of frightful scenes that remind one of bats and broomsticks, though, would be misleading. Mostly, these nuggets (most less than 10 minuts long) jog nostalgia. Casper, star of two segments, was never fond of scaring folks to begin with, and Betty Boop, the other double-billed character, is too cutesie-poo to pull off a portrayal of genuine fear. Still, "Spooky Toons" ought to sit well with fans of the form and those more concerned with old-fashioned fun than Halloween-focused fare, as it trots out some early, largely forgotten gems. [www.amazon.com]
Keywords: DVD-Video